Development of addiction profile index (bapi) clinical form: reliability and validity study - Ögel, Kültegin; Koç, Ceren; Başabak, Aslı; İşmen, E. Mebrure and Görücü, Serap (Journal of Dependence, 2015)
Objective: Addiction is a complicated issue that is accompanied by many mental problems and personality traits. The objective of this study was to develop a questionnaire, which can be used alongside the previously developed Addiction Profile Index (API), to assist in the evaluation of factors affecting addiction. Method: The Addiction Profile Index Clinical Form (BAPI-K), which is intended to be used in conjunction with the original 37-question survey, consists of 21 items that aim to directly measure behavioral factors related to addiction: depression, anxiety, and anger management problems, lack of assertiveness, impulsivity, and novelty seeking behavior. After the questionnaire was developed it was administered to 1087 prisoners. Results: The Cronbach alpha coefficient of the mental health problems section that was added to the API was 0.80, and it ranged from 0.66 to 0.75 for the subscales in this section. When all questions that directly measured addiction, from all sections of the survey, were added to the analysis, the Cronbach alpha coefficient of the whole test was found to be 0.81. Four factors that represented 53% of the total variance were found during the informational factor analysis. The test-retest correlation coefficient was 0.78, and those of the subscales ranged from 0.56 to 0.84. When compared to analyses that were performed using other tests, it was determined that the subscales of the questionnaire showed strong correlations. Conclusion: The Addiction Profile Index Clinical Form was found to be a valid and reliable tool to help in the evaluation of mental health needs of patients with addictions.